PEMBERDAYAAN MASYARAKAT DESA SUNYALANGU DALAM MEMPERSIAPKAN PRODUK KAPULAGA UNTUK PASAR EKSPOR - Gumintang, Bagas; Nikmah, Filda Khoirun; Rafinda, Ascaryan; Suroso, Agus (Jurnal Pengabdian Bisnis dan Akuntansi, 2024)
This community service activity was carried out in Sunyalangu Village with the aim of increasing the capacity and ability of residents in preparing cardamom products so that they are ready for export. The background of this activity is based on the village's abundant economic potential for cardamom commodities, but it has not been optimized for the international market. Through the participatory dialogue method, villagers are directly involved in cardamom digital marketing training. The material presented covered four main aspects: product standardization according to the requirements of export destination countries, product certification management, packaging re-branding and product variations, and international market access. Product standardization aims to ensure cardamom products meet strict international standards, while product certification focuses on official recognition that increases added value and consumer trust. Re-branding of packaging and product variations is designed to increase product attractiveness and diversification in the global market. Finally, the market access strategy aims to expand the range of cardamom products through effective distribution and marketing channels. It is hoped that through this activity, the residents of Sunyalangu Village will be able to improve the quality and competitiveness of their cardamom products in the international market, which can ultimately improve the economic welfare of the village.